Healthcare coverage affects survival of EGFR-mutant Thai lung cancer patients - Khiewngam, Khantong; Oranratnachai, Songporn; Kamprerasart, Kaettipong; Kunakorntham, Patratorn; Sanvarinda, Pimtip; Trachu, Narumol; Pimsa, Pongput; Wiwitkeyoonwong, Jirapath; Thamrongjirapat, Thanaporn; Dejthevaporn, Thitiya; Sirachainan, Ekaphop; Reungwetwattana, Thanyanan (Frontiers in Oncology, 2023)
Background Despite significant benefits of epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) treatment in patients with EGFR-mutated NSCLC, access remains limited in Thailand and elsewhere. Methods Retrospective analysis of patients with locally advanced/recurrent NSCLC and known EGFR mutation (EGFRm) status treated at Ramathibodi Hospital (2012–2017). Prognostic factors for overall survival (OS), including treatment type and healthcare coverage, were analyzed using Cox regression. Results Of 750 patients, 56.3% were EGFRm-positive. After first-line therapy (n=646), 29.4% received no subsequent (second-line) treatment. EGFR-TKI-treated EGFRm-positive patients survived significantly longer than EGFRm-negative patients without EGFR-TKIs (median OS [mOS] 36.4 vs. 11.9 months; hazard ratio HR=0.38 [95%CI 0.32–0.46], P<0.001). Cox regression indicated significantly longer OS in patients with comprehensive healthcare coverage that included reimbursement of EGFR-TKIs, versus basic coverage (mOS 27.2 vs. 18.3 months; adjusted HR=0.73 [95%CI 0.59–0.90]). Compared with best supportive care (BSC; reference), EGFR-TKI-treated patients survived significantly longer (mOS 36.5 months; adjusted HR (aHR)=0.26 [95%CI 0.19–0.34]), and versus chemotherapy alone (14.5 months; aHR=0.60 [95%CI 0.47–0.78]). In EGFRm-positive patients (n=422), relative survival benefit of EGFR-TKI treatment remained highly significant (aHR[EGFR-TKI]=0.19 [95%CI 0.12–0.29]; aHR(chemotherapy only)=0.50 [95%CI 0.30–0.85]; reference:BSC), indicating that healthcare coverage (reimbursement) affected treatment choice and survival. Conclusion Our analysis describes EGFRm prevalence and survival benefit of EGFR-TKI therapy for EGFRm-positive NSCLC patients treated from 2012–2017, one of the largest such Thai datasets. Together with research by others, these findings contributed evidence supporting the decision to broaden erlotinib access on healthcare schemes in Thailand from 2021, demonstrating the value of local real-world outcome data for healthcare policy decision-making.